Effects of the ingestión of Plukenetia volubilis Linneo (a.k.a. 'Sacha inchi') on the lipid profile of young adults - Huamán Saavedra, Juan Jorge (2012)
Introduction: 'Sacha inchi' is the best vegetable source supplying omega-3 (45-55 %), and it is also the main source of unsaturated fatty acids (35-60 %). Objective: To determine if there is any effect of Plukenetia volubilis Linneo ('Sacha inchi') in the lipid panel in young adults. Methods: The study had an experimental design including 28 participants who were medical students between 18 and 25 years old. They were randomly assigned into 2 groups: control and experimental, the second group received 30 grams of Plukenetia volubilis Linneo or 'Sacha inchi' per day for 6 weeks. The lipid panel of all participants was determined using enzymatic methods. Weight and caloric intake were measured at the beginning, and after 3 and 6 weeks of treatment. Results: The control group had the following lipid values at the beginning of the study were as follows: total cholesterol: 175,09 mg/dL; triglycerides: 130,73 mg/dL; HDL cholesterol: 36,78 mg/dL, LDL and cholesterol: 112,16 mg/dL; after 6 weeks, their values were as follows: total cholesterol: 184,87 mg/dL; triglycerides: 123,21mg/dL, HDL cholesterol: 42,04 mg/dL, and LDL cholesterol: 118,19 mg/dL. The experimental group showed the following lipid values at the beginning of the study: total cholesterol: 179,31mg/dl; triglycerides: 123,68 mg/dl, HDL cholesterol: 41,64 mg/dL, and LDL cholesterol: 112.94 mg/dL; after 6 weeks of treatment, their values were: total cholesterol: 155,22 mg/dL; triglycerides: 78,69 mg/dL; HDL cholesterol: 49,54 mg/dL; LDL cholesterol: 89,95 mg/dL. The experimental group showed significant reductions in total cholesterol, 14,02 %, LDL cholesterol, 20,48 %, and triglycerides, 36,37 % with respect to baseline values, and these changes were also significant compared to the control group. There were no significant changes in weight and in the caloric intake. Interpretation: The ingestion of Plukenetia volubilis Linneo or "Sacha inchi" may reduce triglyceride, total cholesterol, and LDL cholesterol, and it increases HDL cholesterol levels in young adults.